Systems-wide effects of short-term feed deprivation in obese mice - Daniel Andersen (Nature Portfolio, 2021)
Abstract While prolonged fasting induces significant metabolic changes in humans and mice, less is known about systems-wide metabolic changes in response to short-term feed deprivation, which is used in experimental animal studies prior to metabolic challenge tests. We here performed a systems biology-based investigation of connections between gut bacterial composition and function, inflammatory and metabolic parameters in the intestine, liver, visceral adipose tissue, blood and urine in high-fat fed, obese mice that were feed deprived up to 12 h. The systems-wide analysis revealed that feed deprivation linked to enhanced intestinal butyric acid production and expression of the gene encoding the pro-thermogenic uncoupling protein UCP1 in visceral adipose tissue of obese mice. Ucp1 expression was also positively associated with Il33 expression in ileum, colon and adipose tissue as well as with the abundance of colonic Porphyromonadaceae, the latter also correlating to cecal butyric acid levels. Collectively, the data highlighted presence of a multi-tiered system of inter-tissue communication involving intestinal, immune and metabolic functions which is affected by feed deprivation in obese mice, thus pointing to careful use of short-feed deprivation in metabolic studies using obese mice.